Heavy quark density in N = 4 SYM: from hedgehog to Lifshitz spacetimes - Prem Kumar (Journal of High Energy Physics, 2012)
We study the effect of an order N^2 density of heavy quarks in strongly coupled N = 4 SUSY Yang-Mills theory in the large N limit. This is achieved in the type IIB supergravity dual by introducing a uniformly smeared density of macro- scopic string sources stretching to the boundary of AdS5 × S5. The backreacted system exhibits a flow from an AdS5 “hedgehog” geometry to a scaling Lifshitz-like solution Lif5×S5 with dynamical critical exponent z = 7, wherein the scaling symme- try is broken by a logarithmic running dilaton. We find an exact black brane solution within the scaling regime which describes the low temperature thermodynamics of the system.